2021
DOI: 10.3390/polym13193389
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Geopolymer Concrete Compressive Strength Using Novel Machine Learning Algorithms

Abstract: The innovation of geopolymer concrete (GPC) plays a vital role not only in reducing the environmental threat but also as an exceptional material for sustainable development. The application of supervised machine learning (ML) algorithms to forecast the mechanical properties of concrete also has a significant role in developing the innovative environment in the field of civil engineering. This study was based on the use of the artificial neural network (ANN), boosting, and AdaBoost ML approaches, based on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 77 publications
0
38
0
Order By: Relevance
“…On the other hand, for ensemble ML techniques, submodels were generated to leverage the weak learner that could be optimized and trained with data for achieving a higher value of R 2 . Other researchers have also observed that AdaBoost, Bagging, and RF models are more accurate in predicting outcomes than individual machine learning techniques [45,50,[59][60][61]. Feng, et al [45] observed that an AdaBoost model outperformed individual models, including an artificial neural network (ANN) and a support vector machine (SVM), in terms of R 2 and error values.…”
Section: Comparison Of Machine Learning Modelsmentioning
confidence: 99%
“…On the other hand, for ensemble ML techniques, submodels were generated to leverage the weak learner that could be optimized and trained with data for achieving a higher value of R 2 . Other researchers have also observed that AdaBoost, Bagging, and RF models are more accurate in predicting outcomes than individual machine learning techniques [45,50,[59][60][61]. Feng, et al [45] observed that an AdaBoost model outperformed individual models, including an artificial neural network (ANN) and a support vector machine (SVM), in terms of R 2 and error values.…”
Section: Comparison Of Machine Learning Modelsmentioning
confidence: 99%
“…The accuracy level between the real and anticipated output was observed from the coefficient correlation (R 2 ) value, and a higher value gives the impressive performance of the employed model. The AdaBoost technique was employed for optimization via producing 20 sub-models to obtain a higher R 2 value [26]. The application of these ML algorithms is to compare the predictive evaluation of each approach.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu, et al [ 40 ] used machine learning to forecast the splitting tensile strength (STS) of concrete containing recycled aggregate (RA) and revealed that the precision level of the bagging model was better. Ahmad, et al [ 41 ] studied the boosting and AdaBoost ML approaches to predict the compressive strength of a high-calcium fly-ash-based geopolymer. Bagging indicated the best results.…”
Section: Resultsmentioning
confidence: 99%